2010
DOI: 10.4049/jimmunol.0903951
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Cells Breaching Self-Tolerance in Autoimmunity

Abstract: Material Supplementary 1.DC1http://www.jimmunol.org/content/suppl/2010/04/21/jimmunol.090395

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…We then investigated whether this failure of T cell help for B cells and the subsequent Ab response were recapitulated in a novel OVA-driven model of RA. We previously described the suggested mode of action of this model in detail (21,(48)(49)(50). Briefly, we think that by transferring a large number of activated Th1 cells of an irrelevant specificity and inducing a local inflammatory stimulus in the joint, the normal regulatory mechanisms are overwhelmed and breach of self-tolerance occurs.…”
Section: Discussionmentioning
confidence: 99%
“…We then investigated whether this failure of T cell help for B cells and the subsequent Ab response were recapitulated in a novel OVA-driven model of RA. We previously described the suggested mode of action of this model in detail (21,(48)(49)(50). Briefly, we think that by transferring a large number of activated Th1 cells of an irrelevant specificity and inducing a local inflammatory stimulus in the joint, the normal regulatory mechanisms are overwhelmed and breach of self-tolerance occurs.…”
Section: Discussionmentioning
confidence: 99%
“…DCs are a very heterogeneous population of cells, and different subsets can have very distinct functions. They are important in the breaching of self-tolerance in autoimmunity,10 and plasmacytoid (p)DCs play an important anti-inflammatory role in the context of articular breach of tolerance 11. It was recently shown that compounds that selectively deplete DCs can ameliorate arthritis12 and that blocking tyrosine kinases may have beneficial effects in arthritis by modulating DC numbers 13.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a possible explanation for the failure to induce arthritis by serum passive transfer could be related to the greater magnitude of anti-CII response than OVA-mediated arthritis and the different antibody specificity rather than the affinity. However, we cannot exclude the possibility that other autoantibodies are required to induce disease or that other cell types, such as T cells or dendritic cells (41), may be necessary to induce arthritis.…”
Section: Discussionmentioning
confidence: 99%